The Use of Twitter in Social Media Marketing: Evidence from Hotels in Asia - Sari, Rora Puspita; Putra, Fajar Kusnadi Kusumah; Maemunah, Ita; Dianawati, Nenden (Department of Management, Faculty of Economics and Business, Brawijaya University, 2022)
The study aims to investigates hotels’ social media marketing practices and how they manage online conversation as well as represent themselves using Twitter. This study employs samples from fifty hotels from 47 countries in Asia, the API method was used to crawl and gather Twitter data. Content analysis was applied to 5438 tweets created by the official hotel Twitter accounts. The results revealed that Twitter was used mostly for five priorities in doing marketing comforts including sales and promotion, introducing and explaining information related to hotel products and services, while were less likely to be used as a medium for handling complaints, creating sales promotions, and sharing light conversation. The findings of this study make an important contribution toward filling the gap in exploring what kind of posts hotels in Asia published on their official Twitter accounts, and how hotels maximize the Twitter platform as digital marketing media and in handling customers’ complaints. This study has shed some light on how hotel marketers effectively manage and take advantage of microblogging sites, in this case the used of Twitter as marketing tools. Further research comparing with bigger data and other countries, or regions will enrich the research findings.